(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Introduction: Maxillary canine is usually the last to erupt in the arch and therefore shows higher chances of impaction. Routinely used radiographic examination for impacted canine is Orthopantomogram (OPG) which has many limitation as it is a two dimensional (2D) image. Recently three dimensional (3D) imaging, Cone Beam Computed Tomography (CBCT), have been introduced which helps us with accurate three dimensional diagnosis of the impacted canine. This study was carried out to compare the radiographic diagnostic accuracy of CBCT with that of panoramic radiography for the localization of impacted maxillary canines. Aims and Objectives: This study was carried out to compare the radiographic diagnostic accuracy of CBCT with that of panoramic radiography for the assessment of the position of impacted maxillary canines by three angular parameters and to determine a formula to get the accurate reading of 3D (CBCT) determined position of impacted canine from a 2D reading for all the three angles. Materials and Method: 30 maxillary impacted canines were studied with standard OPG, CBCT and OPG generated from CBCT. Three angular measurements were studied namely, angle of maxillary impacted canine with the adjacent lateral incisor, occlusal plane and midline in OPG, CBCT and CBCT OPG. Result: CBCT was found to be most accurate of all the three methods for all the three angular measurements. An equation was generated to calculate 3D measurements for all the three angular measurements using a 2D value.